1999
DOI: 10.1590/s0104-42301999000200016
|View full text |Cite
|
Sign up to set email alerts
|

Resposta celular ao estresse

Abstract: Nos últimos dez anos, mais de 10.000 trabalhos científicos foram publicados a respeito das HSP (Heat Shock Proteins), ou proteínas do choque térmico, e da resposta ao choque térmico, ou HSR (Heat Shock Response). Muitos outros vieram à luz focalizando outras respostas celulares ao estresse. O conhecimento destes fenômenos básicos é indispensável à compreensão de inúmeras condições patológicas. As aplicações clínicas são potencialmente muito vastas e podem vir a ser fundamentais em diversas doenças, hoje de dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
13

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 42 publications
(45 reference statements)
0
10
0
13
Order By: Relevance
“…The stress induced the expression of certain genes, which led the cell to produce a certain class of proteins, so-called heat shock proteins. Later, researchers observed that these proteins were expressed in almost all living beings, and not only in response to heat, but also when the cell was exposed to a series of other stressing factors (toxic concentrations of metals, organic pollutants, temperature, osmolarity, hypoxia/anoxia and ultraviolet radiation), and then they began to be called "stress proteins" or "anti-stress proteins" (Meyer & Silva, 1999). Many toxicants affect the correct conformation and consequently, the function of different proteins.…”
Section: Heat Shock Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stress induced the expression of certain genes, which led the cell to produce a certain class of proteins, so-called heat shock proteins. Later, researchers observed that these proteins were expressed in almost all living beings, and not only in response to heat, but also when the cell was exposed to a series of other stressing factors (toxic concentrations of metals, organic pollutants, temperature, osmolarity, hypoxia/anoxia and ultraviolet radiation), and then they began to be called "stress proteins" or "anti-stress proteins" (Meyer & Silva, 1999). Many toxicants affect the correct conformation and consequently, the function of different proteins.…”
Section: Heat Shock Proteinsmentioning
confidence: 99%
“…The HSPs take action, acting as molecular chaperones, since they bind to other proteins, regulating their conformation, movement through the membrane or organelles and enzymatic activity (Calabrese et al, 2005). Therefore, they avoid incorrect interactions between proteins, helping in their synthesis, folding and degradation (Meyer & Silva, 1999). According to Bierkens (2000), HSPs are one of the main cellular markers in the evaluation of the toxicity of different compounds and are widely used to monitor ecosystems.…”
Section: Heat Shock Proteinsmentioning
confidence: 99%
“…HSP70 may be a mobile messenger to transduce nonspecific stress information to the immune system for the initiation of innate immunity and adaptive immunity (Chen and Cao 2010). Because of its chaperone function, HSP70 is also involved in antigen processing and presentation (Cristau et al 1994;Meyer and da Silva 1999). Additionally, Nakhjavani et al (2011) showed that serum eHSP72 level is increased in women with long-standing diabetes compared with men, indicating the existence of some differences of gender/sex.…”
Section: Discussionmentioning
confidence: 99%
“…Recentemente, surgiram evidências de que a lesão dos tecidos não estaria somente limitada à isquemia, podendo se estender ou agravar com a reperfusão 2,3 .…”
unclassified